O ensino da língua inglesa na visão de alunos da escola pública - Bastos, Iara Toledo de Assis (2018)
The purpose of this research is to understand the students' view of the teaching-learning process of the English language, especially the grammar teaching, in the public school of the State of São Paulo. The research was carried out by the teacherresearcher with 36 students of the third year of high school. The data were collected from March to September of 2018 throught a questionnaire and a self assessment. The theoretical assumptions underlying this research are in the works of Leffa (1988), which presents a historical overview of the methodologies of language teaching. Uphoff (2008) and Thornburry (2001) discuss procedures and research on grammar teaching. Dutra (2004), Leffa (2012) and Moita Lopes (1996) bring the reflection to the reality of public education in Brazil. It also focuses on the teaching of foreign languages in Brazil through the National Curriculum for Teaching Foreign Languages (PCN-LE). The results allowed to reflect on pedagogical action that led to a reconstruction of the practice in the classroom.